Juvenile Analysed Based on The Aspect of Morality on The Movie “Alpha Dog” by Nick Cassavetes - Christanto Dwi Nugroho (Deiksis, 2019)
This study is supposed to know the aspect of morality on the movie Alpha Dog by Nick Cassavetes, to know how the form and the function of language use for describing of moral and the use of language to present good and bad character using descriptive qualitative. Having been analyzed the writer comes to the conclusion that bad moral is dominant comparing to good moral. Final the main of character building is parent hands, that good character its part is frontal not to be given from generation but the parents companion is needed is every process of growth especially in the “labil”: condition of kids protected then from juvenile delinquencies. Juvenile delinquency look easy to spend out for the youth, and not to easy to care but it can be one of the danger of a nation, if it is not well cared by parent and society growth.  Keyword : Juvenille delinquency, morality, alpha dog